11th international conference ACAPS (2005)
The 11th international conference ACAPS was held in Paris, October 26-28, 2005. Almost 500 scientists, students, engineers, teachers and coaches from all over the country and abroad (Belgium, Switzerland, Canada, Japan, USA, Germany, Spain, Italy, Australia, etc…) participated in this conference. The conference gave the opportunity to celebrate the 20th anniversary of ACAPS. More than 400 contributions (posters, talks, keynote lectures) in various sub-themes of movement and sport sciences (psychology, ergonomics, neurophysiology, biomechanics, exercise physiology, history, sociology, sport economy, etc) were presented.